2018
DOI: 10.1093/mnras/sty1774
|View full text |Cite
|
Sign up to set email alerts
|

Morphological properties of galaxies in different Local Volume environments

Abstract: We consider an all-sky sample of 1029 Local Volume (LV) galaxies situated within a distance of 11 Mpc. Their majority have precise distances, estimates of hydrogen mass fraction and star-formation rate derived from far-ultraviolet or H α fluxes. To describe an environment, we attribute two dimensionless values: the density contrast created by the most significant neighbour and the local density contrast produced by all neighbours within a separation of 1 Mpc. The hydrogen mass fraction exhibits a weak effect o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 70 publications
(77 reference statements)
0
21
0
Order By: Relevance
“…We combined the above star-formation rate estimates in LV galaxies with similar data for other galaxies located within 11 Mpc. It was already pointed out in Ricciardelli et al [35] and Karachentsev et al [36] that the SFR in late-type galaxies depends only slightly on the neighborhood. The trend of the decrease of SFR from isolated galaxies to group members barely exceeds the dispersion of this quantity and is most manifested among the least massive dwarf galaxies.…”
Section: Resultsmentioning
confidence: 88%
“…We combined the above star-formation rate estimates in LV galaxies with similar data for other galaxies located within 11 Mpc. It was already pointed out in Ricciardelli et al [35] and Karachentsev et al [36] that the SFR in late-type galaxies depends only slightly on the neighborhood. The trend of the decrease of SFR from isolated galaxies to group members barely exceeds the dispersion of this quantity and is most manifested among the least massive dwarf galaxies.…”
Section: Resultsmentioning
confidence: 88%
“…This approach is free from iterations, however, it is applicable only to galaxies with a known rotation amplitude. Considering the statistics of the relation SF R(Hα)/SF R(F U V ) for the Local Volume galaxies, Karachentsev et al (2018) concluded that expression (6) somewhat overestimates the extinction in massive galaxies and underestimates it for dwarf galaxies. In our estimation, the appropriate correction for the internal extinction in late-type spiral disks has the form…”
Section: Resultsmentioning
confidence: 99%
“…We already pointed out above that the closer the dwarf galaxy is to its massive neighbor, the lower is its gas content. The effect of the ambient density on the relative content of hydrogen mass in LV galaxies was analyzed in detail in [53]. To estimate the ambient density, the above authors used three different dimensionless parameters: Θ 1 , the relative local density created by the most circles.…”
Section: H I-properties Of Dwarf Galaxies In Different Environmentsmentioning
confidence: 99%
“…(b) The SF R(Hα)/SF R(F U V ) ratio on the average decreases from spirals to progressively less Dependence of the SF R(Hα)/SF R(F U V ) ratio on other parameters apparent axial ratio of the galaxy, its morphological type, ambient density were analyzed in [53].…”
Section: Star Formation Rate In Dwarfs In Groups and In The Fieldmentioning
confidence: 99%